Synergistic engineering of bromine and cetyltrimethylammonium chloride molecules enabling efficient and stable flexible perovskite solar cells. Issue 37 (14th September 2020) - Mei, Hao; Wu, Yuliang; Wang, Changlei; Ren, Shengqiang; Zhang, Mingdi; Dai, Haitao; Zhao, Dewei; Li, Zhengying; Du, Qingguo; Li, Xiaofeng
Abstract : We report synergetic strategies of combining bromine and cetyltrimethylammonium chloride additives to passivate both bulk and surface defects, leading to improved performance and stability of flexible PVSCs. Abstract : Flexible perovskite solar cells (PVSCs) show promising applications in terrestrial power plant systems irrespective of curved surfaces, but still suffer from low efficiencies and poor stabilities. Here, we report a synergetic strategy of combining bromine (Br) and cetyltrimethylammonium chloride (CTAC) additives to passivate both bulk and surface defects, leading to improved performance and stability of flexible PVSCs. Incorporation of Br suppresses the formation of halide vacancies in the perovskite bulk, while CTAC further modifies the film surface with reduced defects and enhanced hydrophobicity features. As a result, flexible PVSCs with efficiencies over 18% are achieved with high reproducibility, compared to the control devices with efficiencies about 17%. Our flexible PVSCs present excellent ambient stability against moisture, keeping over 90% of the initial efficiency after exposure to 90% humidity for about 170 hours. Our work offers a facile and universal strategy for the fabrication of high performance and stable flexible PVSCs.